A new structural pattern matching algorithm for technology mapping - Zhao, Min; Sapatnekar, Sachin S. (Design Automation, 2001 Proceedings, 2001)
In this paper, a new structural matching algorithm for technology mapping is proposed. The algorithm is based on a key observation that the matches for a node in a subject Boolean network are related to the matches for its children. The structural relationships between the library cells are modeled using a lookup table. The proposed method is fast, has low memory usage, and is easy to implement. Experimental results show speedups of 20x over Matsunaga's fast mapping approach, and orders of magnitude over SIS, with the same or slightly better results, and much lower memory utilization.